Kinetics study of hydrochlorothiazide lactose liquid state interaction using conventional isothermal arrhenius method under basic and neutral conditions (Brazilian Journal of Pharmaceutical Sciences, 2016)
The Maillard reaction of hydrochlorothiazide (HCTZ) and lactose has been previously demonstrated in pharmaceutical formulations. In this study, the activation energy of - hydrohlorothiazide and lactose interaction in the liquid state was ascertained under basic and neutral conditions. Conventional isothermal High Performance Liquid Chromatography (HPLC) technique was employed to ascertain the kinetic parameters using Arrhenius method. Results: The activation energy obtained was 82.43 and 100.28 kJ/mol under basic and neutral conditions, respectively. Consequently, it can be inferred that Maillard reaction is significantly affected by pH, which can be used as a control factor whenever the reaction potentially occurs.